Volume 3: Design and Manufacturing 2007
DOI: 10.1115/imece2007-43473
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive Waterjet Peening With Elastic Prestress: Subsurface Residual Stress Distribution

Abstract: Recent advances in abrasive waterjet (AWJ) technology have resulted in new processes for surface treatment that are capable of introducing compressive residual stresses with simultaneous changes in the surface texture. While the surface residual stress resulting from AWJ peening has been examined, the subsurface residual stress field resulting from this process has not been evaluated. In the present investigation, the subsurface residual stress distribution resulting from AWJ peening of Ti6Al4V and ASTM A228 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Остаточные напряжения первого рода (ОН) существенно влияют на долговечность изделия. Несмотря на высокую эффективность современных методов моделирования, сохраняется необходимость экспериментального измерения остаточных напряжений (деформаций) [1][2][3][4][5][6][7][8][9][10][11][12][13]. Однако большинство механических методов определения ОН являются разрушающими и имеют высокую погрешность (до 40-50%).…”
Section: Introductionunclassified
“…Остаточные напряжения первого рода (ОН) существенно влияют на долговечность изделия. Несмотря на высокую эффективность современных методов моделирования, сохраняется необходимость экспериментального измерения остаточных напряжений (деформаций) [1][2][3][4][5][6][7][8][9][10][11][12][13]. Однако большинство механических методов определения ОН являются разрушающими и имеют высокую погрешность (до 40-50%).…”
Section: Introductionunclassified
“…Due to the complex physical nature the residual stresses simulation and calculations are difficult. The residual stress is researched by experimental methods [4], including strain gauges methods [5], strain evaluation during residual stresses relaxation [6], the material hardened layers layer-by-layer chemical removal with the occurring strain estimation [4], X-ray diffraction [7] and microindentation [8] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The surface residual stress ranged from 680 to 1487 MPa for Ti6Al4V and 720 to 1554 MPa for ASTM A228 steel; the depth ranged from 265 to 370 μm for Ti6Al4V and 550 to 680 μm for ASTM A228 steel. Results showed that elastic prestress may be used to increase the surface residual stress in AWJ peened components by up to 100 % [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers agree that it is important to measure, evaluate, predict and control their magnitude and distribution of residual stresses. Residual stresses are investigated by experimental methods, including tensometry [2], evaluation of deformations in the relaxation of residual stresses [5], by layer-by-layer chemical removal of hardened material layers with an estimation of the emerging deformation [5], X-ray diffraction [7], microindentation [8] and others.…”
Section: Introductionmentioning
confidence: 99%